Plant Growth Promotion Assessment in Rice Plant Enhanced by Inoculation of Rhizobacteria - Shrivastava, Umesh Prasad (Academic Voices: A Multidisciplinary Journal, 2015)
In the search of efficient biofertilizer, nine efficient strains of PGPR were evaluated by inoculation in two different rice varieties, Saryu-52 and Malviya Dhan-36 in the gnotobiotic conditions using two different media FCN-medium and soil extract medium. Agrobacterium sp. strain BN-2A showed better result in respect to other eight isolates in the total length, fresh weight, number of roots and chlorophyll-a content. By the inoculation Agrobacterium sp. strain BN-2A, total length increased in Saryu-52 (22.6%) and in Malviya Dhan-36 (52.1%), fresh weight increased in Saryu-52 (42.4%) and in Malviya Dhan-36 (68.8%) and chlorophyll-a increased in Saryu-52 (76.6%) and in Malviya Dhan-36 (37.1%). Similarly in soil extract medium, inoculation of Agrobacterium sp. strain BN-2A alone showed better result in comparison to mixture of nine strains. To prove that colonization indeed occurs, gusA reporter gene was tagged with the most efficient isolate Agrobacterium sp. strain BN-2A and colonization in the rice root was confirmed by gusA staining and histochemical analysis of gusA staining. Therefore, BN-2A has best potential to be used as biofertilizer. DOI: http://dx.doi.org/10.3126/av.v4i0.12362 Academic Voices Vol.4 2014: 73-84